Digestão total e pré-cecal dos nutrientes em potros fistulados no íleo - De Almeida Oliveira, Ana Alix Mendes [UNESP]; De Queiroz, Augusto César; Valadares Filho, Sebastião De Campos; Leão, Maria Ignez; Cecon, Paulo Roberto; Pereira, José Carlos (My University, 1998)
Six male colts, 1/2 blood Breton-Campolina ileum fistulated were ad libitum fed with three rations: R1: elephant grass; R2: elephant grass plus ground corn, and R3: elephantgrass plus ground corn plus soybean meal, aiming: 1) to estimate and compare the total apparent digestibility of dry matter (DM), obtained by the marker chromic oxide and the total collection of feces, 2) to evaluate the pre-cecal and post-ileal apparent digestibility of DM, organic matter (OM), crude protein (CP), and neutral detergent fiber (NDF), for the three diets and 3) to calculate, for difference, the energy and protein values of corn and its combination with the soybean meal for equine. A descriptive analysis was made for all the observed values. The estimate coefficients of apparent digestibility, for the three diets, using chromic oxide underestimated the values obtained by total feces collection. Highest values of apparent digestibility for OM and CP and fiber constituents of cellular wall were found, when soybean meal was added to the elephant grass and to the ground corn (R3). The apparent digestibility ether extract was as much similar for the corn (R2) as for corn plus soybean meal (R3). The elephant grass had low values of pre-cecal and post-ileal apparent digestibility. The pre-cecal apparent digestibility of CP, in the diet 2, was lower than the diet 3 and higher for DM. The digestibility pre-ileal of NDF, in the diet 2, was higher than that of the diet 3. The sites of digestion of CP, NDF, DM and OM were influenced by diets, being the small intestine the site more active in the digestion of protein and the large intestine, the most active site for the digestion of fiber.
Total and pre-cecal digestion of the nutrients in colts ileum fistulated
Keywords: Apparent digestibility; Elephantgrass; Equine; Fistula; Post-ileal; Prececal